2006
DOI: 10.1007/s10533-005-5273-1
|View full text |Cite
|
Sign up to set email alerts
|

Soil Properties and their Spatial Pattern in a Degraded Sandy Grassland under Post-grazing Restoration, Inner Mongolia, Northern China

Abstract: In this study, we use classical and geostatistical methods to identify characteristics of some selected soil properties including soil particle size distribution, soil organic carbon, total nitrogen, pH and electrical conductivity and their spatial variation in a 5-year recovery degraded sandy grassland after two different grazing intensity disturbance: post-heavy-grazing restoration grassland (HGR) and post-moderately grazing restoration grassland (MGR), respectively, in Horqin steppe, Inner Mongolia, norther… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
56
3

Year Published

2009
2009
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 93 publications
(64 citation statements)
references
References 25 publications
5
56
3
Order By: Relevance
“…Nevertheless, this area is typical of a Tibetan grassland landscape and climate. Because general changes in functional gene compositions of the microbial community are modified by local, regional, and temporal variations (Lin et al 2010;Su et al 2006), it would be interesting to expand the observations in this study to other grasslands or conduct time-series experiments to test the generality of these observations.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, this area is typical of a Tibetan grassland landscape and climate. Because general changes in functional gene compositions of the microbial community are modified by local, regional, and temporal variations (Lin et al 2010;Su et al 2006), it would be interesting to expand the observations in this study to other grasslands or conduct time-series experiments to test the generality of these observations.…”
Section: Discussionmentioning
confidence: 99%
“…Soil disturbance alters both the physical characteristics (surface temperature, albedo, moisture dynamics) and nutritional resource distribution in desert soils (Belnap and Eldridge, 2003;Su et al, 2006). Spatial distribution of soil nutrients, in part, controls the distribution of bacterial communities across multiple scales (Franklin and Mills, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…Because in similar studies the spherical model was shown to provide an adequate representation of the spatial variability of soil data (Schlesinger et al 1996;Su et al 2006;Wang et al 2007c), in this study the semivariograms of all the variables at the wet site (Mongu) were fitted by a spherical model. However, for the Tshane site the exponential model provides a better fit of the soil δ 15 N data both in terms of shape and R-square value.…”
Section: Discussionmentioning
confidence: 99%